Gigabit access: Germany lags behind in international comparison but demand is low - Yann Girard; Anselm Mattes; Claus Michelsen (DIW Weekly Report, 2018)
Broadband internet expansion is a topic of widespread discussion in Germany right now. But the country still has not met its own targets. Almost 100 percent of households are supplied with broadband connections with up to six megabits per second, yet Germany has lots of room to catch up when it comes to gigabit-capable connections-particularly in sparsely populated regions. On the demand side, copper cable connections are the technology with the largest market share. At between one and two percent, pure fiber-optic connections only play a minor role. In international comparison, Germany's need to get up to speed becomes very obvious. The OECD average for fiber-optic connection demand is 21 percent of the overall broadband market. Currently, a relatively low willingness to pay and high investment costs are slowing down the momentum of both demand and supply in Germany. But demand is on a constant growth course. In order to develop a full-coverage gigabit infrastructure by 2025, the government should aim for a well-balanced combination of regulatory incentives for private sector investments and effective subsidies to cover 'blank spots'.
Keywords: L5; L96; O18; 330; broadband; fiber optic; regulation; infrastructure; telecommunication; digitization